PENERAPAN METODE FUZZY DALAM PENENTUAN PRIORITAS PENGURANGAN PEMBOROSAN (WASTE) DENGAN PENDEKATAN LEAN DI UNIT RAWAT JALAN SUATU RUMAH SAKIT - Rumayar, Christania Putri; Mulyana, Ig. Jaka; Trihastuti, Dian; Kosasih, Wilson (Universitas Tarumanagara, 2025)
Hospitals are health facilities that provide medical services and care for patients. Every hospital is always required to maintain and quality of service in order to achieve customer satisfaction and improve efficiency. Lean Management can be used as an approach to improve service quality and efficiency. The first step of improvement is to identify waste in the hospital. This article aims to discuss identification of waste in the outpatient unit of a hospital. Furthermore, determine the priority of waste that must be reduced (eliminated). The methods used are observation, interview and fuzzy. The results showed that the waste that is prioritized to be reduced (eliminated) are patients waiting for the next process (W2), the process of supplying repetitive drugs (OVP2), and patients waiting for registration (W1). The results of this study can be used by hospital management as a reference for making improvements, both in the outpatient unit and other service units.